Monitoring the Autonomic Nervous Activity as the Objective Evaluation of Music Therapy for Severely and Multiply Disabled Children - Orita, Makiko; Hayashida, Naomi; Shinkawa, Tetsuko; Kudo, Takashi; Koga, Mikitoshi; Togo, Michita; Katayama, Sotetsu; Hiramatsu, Kozaburo; Mori, Shunsuke; Takamura, Noboru (The Tohoku Journal of Experimental Medicine, 2012)
Severely and multiply disabled children (SMDC) are frequently affected in more than one area of development, resulting in multiple disabilities. The aim of the study was to evaluate the efficacy of music therapy in SMDC using monitoring changes in the autonomic nervous system, by the frequency domain analysis of heart rate variability. We studied six patients with SMDC (3 patients with cerebral palsy, 1 patient with posttraumatic syndrome after head injury, 1 patient with herpes encephalitis sequelae, and 1 patient with Lennox-Gastaut syndrome characterized by frequent seizures, developmental delay and psychological and behavioral problems), aged 18-26 (mean 22.5 ± 3.5). By frequency domain method using electrocardiography, we measured the high frequency (HF; with a frequency ranging from 0.15 to 0.4 Hz), which represents parasympathetic activity, the low frequency/high frequency ratio, which represents sympathetic activity between the sympathetic and parasympathetic activities, and heart rate. A music therapist performed therapy to all patients through the piano playing for 50 min. We monitored each study participant for 150 min before therapy, 50 min during therapy, and 10 min after therapy. Interestingly, four of 6 patients showed significantly lower HF components during music therapy than before therapy, suggesting that these four patients might react to music therapy through the suppression of parasympathetic nervous activities. Thus, music therapy can suppress parasympathetic nervous activities in some patients with SMDC. The monitoring changes in the autonomic nervous activities could be a powerful tool for the objective evaluation of music therapy in patients with SMDC.